2006
DOI: 10.1002/jcb.20915
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of resistin in osteoblasts and osteoclasts indicate a role in bone metabolism

Abstract: The adipose tissue is the site of expression and secretion of a range of biologically active proteins, called adipokines, for example, leptin, adiponectin, and resistin. Leptin has previously been shown to be expressed in osteoblasts and to promote bone mineralization, whereas adiponectin expression is enhanced during osteoblast differentiation. In the present study we explored the possible role of resistin in bone metabolism. We found that resistin is expressed in murine preosteoclasts and preosteoblasts (RAW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
2
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(162 citation statements)
references
References 35 publications
3
142
2
9
Order By: Relevance
“…Resistin stimulates osteoclast differentiation and NF-κB activity, the major signaling pathway involved in osteoclastogenesis. The observed, although weak, decrease in the RANKL/OPG mRNA ratio may indicate an indirect inhibitory effect, while an increase in IL-6 secretion may result in a stimulatory effect on osteoclastogenesis [118]. In one study, resistin levels correlated with a marker of bone metabolism, carboxyterminal cross-linked telopeptide of type I collagen (ICTP), while it was inversely related with bone mineral density [101].…”
Section: Resistin and Bone Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistin stimulates osteoclast differentiation and NF-κB activity, the major signaling pathway involved in osteoclastogenesis. The observed, although weak, decrease in the RANKL/OPG mRNA ratio may indicate an indirect inhibitory effect, while an increase in IL-6 secretion may result in a stimulatory effect on osteoclastogenesis [118]. In one study, resistin levels correlated with a marker of bone metabolism, carboxyterminal cross-linked telopeptide of type I collagen (ICTP), while it was inversely related with bone mineral density [101].…”
Section: Resistin and Bone Metabolismmentioning
confidence: 99%
“…Resistin expression has been found in murine preosteoblasts, preosteoclasts, and in primary human bone marrow stem cells, as well as in mature human osteoblasts [118]. Resistin stimulates osteoclast differentiation and NF-κB activity, the major signaling pathway involved in osteoclastogenesis.…”
Section: Resistin and Bone Metabolismmentioning
confidence: 99%
“…Major down-regulated proteins in the bone metastatic lesion include apolipoprotein E, whose deficiency has been reported in the context of a reduction of bone formation 50 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 osteolysis 53 , resistin, which is known to increase osteoclastogenesis 54 , and prothrombin, which is overexpressed during osteoclastogenesis in rodents. 55 Among the proteins expressed in the bone metastase and the breast primary lesion, we noticed that the small leucine-rich proteoglycan (SLRP) family was well represented.…”
Section: Differentially Expressed Proteins Involved In Cell Migrationmentioning
confidence: 99%
“…86 31 RETN Resistin ↑ Resistin increased the number of differentiated osteoclasts and stimulated NFkappaB promoter activity, indicating a role in osteoclastogenesis. 54 32 F2 Prothrombin ↑ Prothrombin expression is increased during rodent osteoclastogenesis. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 …”
Section: Alpcmentioning
confidence: 99%
“…Kanazawa et al [36] demonstrated that ADIPO and AMP kinase activator stimulated the proliferation, differentiation, and mineralisation of MC3T3-E1 cells, while Luo et al [37,38] concluded that ADIPO stimulated human osteoblasts proliferation and differentiation and inhibited OPG expression in human osteoblasts via the MAPK signalling pathway. Thommesen et al [39] found enhanced RES expression in murine osteoclast and osteoblasts precursor cells (RAW 264.7, MC3T3-E1) and in primary human bone marrow stem cells. The expression of resistin mRNA in RAW 264.7, increased during differentiation, seemed to be regulated through PKC-and PKA-dependent mechanisms.…”
Section: Introductionmentioning
confidence: 99%